Tra ludo zannesco e commedia dell'arte: Lo spettacolo del veneziano Giovanni Tabarino nell'Ungheria cinquecentesca - Draskóczy, Eszter (Verbum – Analecta Neolatina, 2007)
A short description of a buffonesque performance is contained in a manuscript (Fol. Lat. 3606/III) of the National Library of Hungary, formerly owned by Miklós Istvánffy, a Hungarian statesman and poet of the late 16th century. The study identifies the performer as Giovanni Tabarino, an actor of commedia dell'arte at the court of Emperor Maximilian II, and situates it in the context of contemporary comic performances. The text itself and a parallel passage fromamanuscript poemof Johannes Stabius a Dubnice are included in the appendix.